The SDS and Wisconsin State University Eau Claire - Runnoe, Seth (My University, 2011)
The Wisconsin State University Eau Claire was affected by the 1960's just like the rest of the nation. In 1967 the Students for a Democratic Society established a presence on the Eau Claire campus. The SDS wished to obtain a university charter and be recognized as a student organization at the university. The potential charter placed pressure on the faculty and administration; pressure that was placed by the community. This paper will explain the origins of the SDS, how it spread, and the impact it had on the Eau Claire campus and community.
Keywords: Students for a Democratic Society (U.S.). Eau Claire Wisconsin Chapter; Wisconsin State University, Eau Claire--Political activity; Wisconsin State University, Eau Claire--Students--Societies, etc.